219PLong-term outcomes of bladder preservation in muscle-invasive bladder cancer patients. (24th November 2019) - Satiti, A D; Mistry, H; Song, Y P; Choudhury, A
Abstract: Background: Radical radiotherapy is the mainstay of bladder preservation treatment for muscle-invasive bladder cancer (MIBC) patients. The concurrent use of radiosensitisers improves patient outcome (Caffo et al., 2016, Hoskin et al., 2010). However, different factors may preclude patients from receiving radiosensitisers. This retrospective study evaluates the survival and toxicity outcomes of bladder preservation treatment in a tertiary cancer centre. Methods: Patients treated with radical radiotherapy from 2010 to 2017 were divided into two groups depending on whether they received radiosensitisers in addition to radiotherapy. The primary outcome was overall survival (OS) and the secondary outcome was rate of late toxicities. Kaplan-Meier analyses were used to analyse OS. Late genitourinary (GU) and gastrointestinal (GI) toxicities were defined as treatment-related toxicities at 1-year post-treatment, assessed on the LENT/SOMA scale. Results: A total of 428 patients were included in the survival analysis. 303 patients had combination treatment while 125 patients had radiotherapy alone. Patients in the combination group were younger (median age 72 vs 81, p < 0.001), have better performance status (PS 0-2 298 (95%) vs 115 (92%), p < 0.001), and fewer comorbidities compared to patients in radiotherapy alone group. The median follow-up for this study was 56 months. The median OS was 76 months (95% CI: 66-NA) in radiosensitiser group compared to 13 months in radiotherapy only group (95% CI: 13-21) (p < 0.001, HR = 3.09 (95% CI: 2.32-4.12)). As shown in the table, the incidence of late toxicity was low in both groups and formal analysis could not be carried out. Conclusions: The survival outcome with radiosensitisation in this real-world retrospective study is in keeping with published data. Bladder preservation is effective with minimal long-term toxicities. Patients with localised MIBC should be offered the option of bladder preservation treatment. Legal entity responsible for the study: Radiotherapy-Related Research Group, The Christie Hospital NHS Foundation Trust. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.